Vazios Urbanos e a Produção Espacial Contemporânea: Uma análise do urbanismo neoliberal em Belo Horizonte - Nuno Gabriel Resende Correia Neves (2019)
The objective of the following study is to analise one of the (very often) forgotten spaces of the city: the urban voids. In an attempt to grasp them in their economic, political and social dimension we will make a brief analysis on the changes implemented on the urban design policies in the last few decades. In this way, we will divide this thesis in two main chapters: on the first one we will make a critical analysis on the ascencion of the neoliberal discourse in the tools of urban planning and city management. We will see what exactly is the neoliberalism ideology, allocating it historically and contextualy. With this frame we will see how this new way of the world 1 penetrates our experience of the daily and community life and how it installs itself in urban planning decisions. After a critical reading of the Operações Urbanas Consorciadas, one of the main modalities of PPP adopted by the brazillian government since the 1990s, we will be able to comprehend which dynamics these tools solidifies and which they eliminate, understanting the urban landscape in all its diversity and multiplicity as well as with all its actors ( living and non-living ) involved in the process. This work will focus on the case of a brazillian city, Belo Horizonte, and we will see how the city is a stage of conflict between many agents and how, in the neoliberal context, the city is always territory in contest 2. With a "common ground" built in these first chapter we can follow with the second chapter, where we will analise the theme of the urban voids in an attempt to understand where does its resilience come from and what are the urban economic conditions for its development.